Prevalence of peripheral neuropathy and associated risk factors in children with type 1 diabetes. Issue 2 (April 2022) - Singh, Indrabhushan; Reddy, Chaithanya; Saini, Arushi Gahlot; Dayal, Devi; Sharawat, Indar Kumar; Kasinathan, Ananthanarayanan; Sachdeva, Naresh; Attri, Savita; Sankhyan, Naveen
Highlights: 91% of children with TID may have electrophysiological abnormalities. 18% of children with T1D develop subclinical neuropathy. Most common pattern of neuropathy in children is pure motor type. Body mass index is an important predictor of neuropathy in children. Nerve conduction should be performed to look for nerve dysfunction and progression. Abstract: Aim: To detect the prevalence of diabetic polyneuropathy (DPN) in children with type 1 diabetes (T1D) and to identify associated the risk factors. Methods: This cross-sectional study evaluated children aged between 2 and 16y with T1D for ≥2 y. Detailed neurological examination, neuropathy symptom score, and nerve conduction studies were done in all children to assess nerve dysfunction. Disease-related factors were evaluated for the prediction of neuropathy. Results: Sixty-six children (67% boys) were enrolled. The mean age at the time of diagnosis of T1D was 7.1 ± 2.6 years. The mean duration of diabetes was 4 ± 1.8 years. None of the patients had neuropathy on clinical examination or on the neuropathy symptom score. The prevalence of subclinical DPN was 18.2% (n = 12/66). The type of neuropathy was pure motor (n = 11, 91.6%) and mixed sensorimotor (n = 1, 8.3%). The common peroneal nerve was most commonly affected (n = 6, 50%), followed by the tibial (n = 4, 33.3%) nerve. The most common patterns of nerve involvement were mixed axonal and demyelination (n = 7, 58.3%), followed by axonal (n = 3, 25%) and demyelinating type (n = 2, 16.6%). Children with subclinical DPN had a significant reduction in velocity of tibial, common peroneal, median motor, and ulnar motor nerves; delayed latency in common peroneal, median motor, ulnar motor, and median sensory nerves compared to those without DPN (p value <0.05). A higher body mass index predicted the development of subclinical DPN (p value <0.05). Conclusion: Nearly one-fifth of children with T1D have subclinical neuropathy as early as two years of the disease. A higher body mass index is significantly associated with DPN. Electrophysiological studies should be performed regularly to screen for nerve dysfunction and its progression.